Emerging soluble organic redox materials for next-generation grid energy-storage applications. (June 2020) - Zhan, Xiaowen; Lu, Xiaochuan; Reed, David M.; Sprenkle, Vincent L.; Li, Guosheng
Abstract : Abstract: Because of their structural versatility, fast redox reactivity, high storage capacity, sustainability, and environmental friendliness, soluble organic redox molecules have emerged as materials that have potential for use in energy-storage systems. Considering these advantages, this paper reviews recent progress in implementing such materials in aqueous soluble organic redox flow batteries and organic alkali metal/air batteries. We identify and discuss major challenges associated with molecular structures, cell configurations, and electrochemical parameters. Hopefully, we provide a general guidance for the future development of soluble organic redox materials for emerging energy-storage devices used in the electricity grid.